Kajian Visualisasi Karakter dalam Seri Komik Garudayana - Mikha Widy; Alvanov Zpalanzani Mansoor; Naomi Haswanto (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2013)
The invasion of Japanese pop culture since 1990's influences contemporary visual art and design development especially comics in Indonesia. Popularity of Japanese comic or manga incites Indonesia's comics that adapting Japanese manga visual style. One of Indonesia's comic which influence by manga is Garudayana. Garudayana adopt storyplot and manga-esque style; however Garudayana still elaborates wayang storyplot from Indonesian tradition, but in different perspective. The creator elaborates wayang purwa, the prequel story of Mahabharata, the ingeneous wayang storyplot. Is Yuniarto the Garudayana creator compose manga-esque style with wayang purwa setting, and redesign the custom wayang character.This study aims to develop understandings the creative processes and production stages, especially in characters' design. The study used observation towards published Garudayana comic series,in depth interview with the creator, and literature studies on wayang and character design theories. The study finding the strong points of Garudayana based on creator's understanding of manga , his ability to combine, and adapt in elaborating cultural content wayang purwa storyline.